Denture acceptance among newly rehabilitated elderly population in old age homes in South India - Shetty, Mallika S. (Contemp Clin Dent, 2015)
INTRODUCTION: Elders in old age homes are mainly those who have been abandoned by their family and have one or more physical or mental disabilities. It is a major challenge for the dental professional to plan oral health strategy for this group of patients. AIM OF THE STUDY: Aim of the present study is to observe and determine the acceptance of new dental prosthesis among the elderly residing as inmates of 3 old age homes in Mangalore City. MATERIALS AND METHODS: This cross-sectional study was conducted using a survey proforma. Information regarding their experience with the new denture, 1-month, 3 months and 6 months after denture insertion was gathered. Statistical analysis of the data was done using the Chi-square test with the P < 0.05 considered significant. RESULTS: One hundred and eighty-three residents out of a total of 400 residents in 3 old age homes were denture wearers. Among them, 101 (55.2%) were females, and 82 (44.8%) were males. Dental prosthesis whether worn regularly, discomfort, retention, cleansing of denture during a period of 1-month, 3 months and 6 months was found to be significant satisfaction with the prosthesis, denture adhesives used, food accumulation during a period of 1-month, 3 months and 6 months was found to be nonsignificant. CONCLUSION: The emotional makeup of the patient must be taken into consideration during the entire procedure. We must understand that the success of the prosthesis depends mainly on the patient's confidence in the dentist rather than the quality of the prosthesis.